2019
DOI: 10.1177/1368430219826683
|View full text |Cite
|
Sign up to set email alerts
|

Sexism, perceived discrimination, and system justification in the 2016 U.S. presidential election context

Abstract: The 2016 U.S. presidential election provided a pertinent context for investigating novel influences on system-related beliefs. We examined Trump and Clinton supporters’ sexist attitudes toward women, perceptions of gender discrimination, and system justification before and after the election. Controlling for conservatism, we found that (a) Trump supporters reported more modern and hostile sexism than Clinton supporters; (b) male Trump supporters perceived greater gender discrimination toward men than male Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…However, men report more personal adherence to SDS (Alison and Risman, 2013; England and Bearak, 2014) and higher scores in the SDSS-S than women (Sierra et al, 2018). There is evidence that beliefs related to the system (Jost et al, 2017) and sexism (Gómez-Berrocal et al, 2011; Monteith and Hildebrand, 2019) shape both individual and group perceptions of gender discrimination. Future research should examine in more depth the role of these processes in individual support for the SDS and in society’s perception of the SDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, men report more personal adherence to SDS (Alison and Risman, 2013; England and Bearak, 2014) and higher scores in the SDSS-S than women (Sierra et al, 2018). There is evidence that beliefs related to the system (Jost et al, 2017) and sexism (Gómez-Berrocal et al, 2011; Monteith and Hildebrand, 2019) shape both individual and group perceptions of gender discrimination. Future research should examine in more depth the role of these processes in individual support for the SDS and in society’s perception of the SDS.…”
Section: Discussionmentioning
confidence: 99%
“…Women who become mothers tend to fall behind, whereas men who become fathers often do even better than men who don't become fathers (Aravena, 2015;Cudd, 2006, chap. 5;Miller, 2014; see also Lisa and Larry example in Ayala-López and Beeghly, Chapter 11, "Explaining Injustice: Structural Analysis, Bias, and Individuals"). (Parenthood is not the only factor behind the gender pay gap.…”
Section: Leaving Mothers Behindmentioning
confidence: 99%
“…If views like these remain pervasive, how can we expect to generate enough enthusiasm and buy-in to make meaningful and durable changes to parenting policies? The fundamental reason that it doesn't make sense to say things like, "don't worry about individuals' prejudices and stereotypes, just focus on changing structures," is that individuals' prejudices and stereotypes are some of the most powerful factors shaping their willingness to support (or oppose) political and structural change (Azevedo et al, 2019;Cooley et al, 2019;Harell et al, 2016;Monteith and Hildebrand, 2019;Mutz, 2018).…”
Section: Either/or Versus Both/andmentioning
confidence: 99%
“…Many scholars simply do not observe considerable bias against majority groups in society. Indeed, this idea is supported by the 2016 ANES data; even Trump supporters view discrimination against women as occurring more often than discrimination against men (Monteith and Hildebrand 2019;Zigerell 2019). Even among those most predisposed to believe that discrimination against men is occurring, discrimination against women still is perceived as more prevalent in society.…”
mentioning
confidence: 99%
“…It is accurate to state that considerable research has found that sexism negatively influenced Clinton's 2016 presidential campaign (Cassese and Holman 2019;Knuckey 2019;Monteith and Hildebrand 2019;Schaffner, MacWilliams, and Nteta 2018;Valentino, Wayne, and Oceno 2018). However, these findings are not without critique; Zigerell (2019) claimed that current measurements of sexism measure bias only toward women and do not account for anti-man bias.…”
mentioning
confidence: 99%